Socio-Technical Systems: Conceptual and Implementation Problems - Maton, Bob (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
This paper explores possible reasons for the resistance by both workers and managers to introduction of the STS approach, despite its apparent benefits to both.